CFH I62V as a Putative Genetic Marker for Posner-Schlossman Syndrome - Yang, Ming Ming; Sun, Hong Yan; Meng, Ting; Qiu, Shan Hu; Zeng, Qi Qiao; Ng, Tsz Kin; Jiang, Li; Deng, Ting Ming; Zeng, Ai Neng; Wang, Jun; Luo, Xiao Ling (Frontiers in Immunology, 2021)
Objective: Posner-Schlossman syndrome (PSS), also known as glaucomatocyclitic crisis, is an ocular condition characterized by recurrent attacks of anterior uveitis and raised intraocular pressure. Previous studies by our team and others have identified the genetic association of complement pathway genes with uveitis and glaucoma. This study aimed to investigate the complement genes in PSS patients with the view of elucidating the genetic background of the disease. Methods: A total of 331 subjects (56 PSS patients and 275 controls) were recruited for this study. We selected 27 variants in six complement pathway genes (SERPING1, C2, CFB, CFH, C3, and C5) and detected them using TaqMan single nucleotide polymorphism (SNP) Genotyping Assays. Univariate SNP association analysis, haplotype-based association analysis, gene-gene interaction analysis among complement genes, and genotype-phenotype correlation analysis were performed. Results: Among the 27 variants of six complement pathway genes, the functional variant I62V (rs800292) at the CFH gene was found to be significantly associated with PSS; there was a significant increase in the frequency of A allele and AA homozygosity in PSS patients than in controls (P=1.79×10-4; odds ratio (OR) 2.18, 95% CI: 1.44-3.29; P=4.65×10-4; OR 3.66, 95% CI: 1.70-7.85, respectively). The additive effect of CFH-rs800292 and SERPING1-rs3824988 was identified with an OR of 12.50 (95% CI: 2.16-72.28). Genotype-phenotype analysis indicated that the rs800292 AA genotype was associated with a higher intraocular pressure and higher frequency of recurrence. Unlike a high proportion of human leukocyte antigen (HLA)-B27 positivity in anterior uveitis, only 3 in 56 (5.36%) PSS patients were HLA-B27 positive. In addition, one haplotype block (GC) in the SERPING1 gene showed a nominal association with PSS with an increased risk of 2.04 (P=0.01; 95% CI: 1.18-3.53), but the P-value could not withstand the Bonferroni correction (Pcorr > 0.05). Conclusion: This study revealed a genetic association of a CFH variant with PSS as well as its clinical parameters, implying that the alternative complement pathway might play an important role in the pathogenesis of PSS. Further studies to enrich the understanding of the genetic background of PSS and the role of the complement system in ocular inflammation are warranted.